Neuronavigated Repetitive Transcranial Stimulation Improves Neurocognitive Functioning in Veterans with Schizophrenia: A Possible Role of BDNF Polymorphism - Su, Xiuru; Liu, Haixia; Wang, Xuan; Pan, Xiuling; Zhang, Xuan; Lu, Xinyan; Zhao, Long; Chen, Yingnan; Shang, Yujie; Wu, Fengchun; Xiu, Meihong (Current Neuropharmacology, 2023)
It has been reported in the previous literatures that high-frequency (HF) neuronavigated repetitive transcranial magnetic stimulation (rTMS) may improve neurocognitive functioning in patients with schizophrenia. Nonetheless, the heterogeneity of the research findings with regards to the effectiveness of HF-rTMS on the neurocognitive functioning in patients with schizophrenia greatly hinders its clinical application. The current study was designed to determine the predictive role of BDNF variants for neurocognitive improvements after rTMS administration in veterans with schizophrenia. 109 hospitalized veterans with schizophrenia were randomly allocated to active HF-rTMS (n=63) or sham stimulation (n=46) over left DLPFC for 4 consecutive weeks. Neurocognitive functions were assessed by using the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) at baseline and at the end of week 4. BDNF polymorphism was genotyped by the technicians. Compared with sham stimulation sessions, the immediate memory performance was significantly increased in active sessions after neuronavigated HF-rTMS administration. In addition, patients with the CC homozygotes demonstrated greater improvement of immediate memory after rTMS treatment, while T allele carriers showed no significant improvement in immediate memory domain relative to baseline performance of immediate memory. Our findings suggest that add-on neuronavigated HF-rTMS is beneficial on immediate memory only in patients with CC homozygotes, but not in T allele carriers. This pilot study provides further evidence for BDNF as a promise biomarker in predicting the clinical response to rTMS stimulation.
Keywords: rTMS